2009
DOI: 10.1128/aem.02255-08
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity of Infectious Red Sea Bream Iridovirus Isolates from Cultured Fish in Japan

Abstract: Megalocytivirus is causing economically serious mass mortality by infecting fish in and around the Pacific region of Asia. The recent emergence of many new iridoviruses has drawn attention to the marked taxonomic variation within this virus family. Most studies of these viruses have not included extensive study of these emergent species. We explored the emergence of red sea bream iridovirus (RSIV) on a fish farm in Japan, and we specifically endeavored to quantify genetic and phenotypic differences between RSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…Given the high sequence identity for several key genes, including for MCP and ATPase, all other described megalocytiviruses are currently considered strains of ISKNV. The results of our phylogenetic analysis are in good agreement with previous phylogenetic analyses aimed at understanding the relationships of these ISKNV strains (Sudt hongkong et al 2002a, Do et al 2005a,b, Nakajima & Kurita 2005, Go et al 2006, Imajoh et al 2007, Wang et al 2007, Song et al 2008, Shinmoto et al 2009, Weber et al 2009, Dong et al 2010, Shi et al 2010. Interestingly, TSIV has the greatest genetic distance from the rest of the ISKNV strains (Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given the high sequence identity for several key genes, including for MCP and ATPase, all other described megalocytiviruses are currently considered strains of ISKNV. The results of our phylogenetic analysis are in good agreement with previous phylogenetic analyses aimed at understanding the relationships of these ISKNV strains (Sudt hongkong et al 2002a, Do et al 2005a,b, Nakajima & Kurita 2005, Go et al 2006, Imajoh et al 2007, Wang et al 2007, Song et al 2008, Shinmoto et al 2009, Weber et al 2009, Dong et al 2010, Shi et al 2010. Interestingly, TSIV has the greatest genetic distance from the rest of the ISKNV strains (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Genomic sequence information and numerous subsequent analyses have revealed that megalocytiviruses from a wide range of hosts share a high level of sequence homology, with 97% or greater identity at the deduced amino-acid level for the major capsid protein (Smail & Munro 2001, Wang et al 2007). The generation of genomic sequence information for mega locytiviruses has prompted numerous phylogenetic analyses (Sudthongkong et al 2002a, Do et al 2005a,b, Nakajima & Kurita 2005, Go et al 2006, Imajoh et al 2007, Wang et al 2007, Song et al 2008, Shinmoto et al 2009, Weber et al 2009, Dong et al 2010, Kim et al 2010. Although the datasets, inclusion of taxa, methods, and interpretation of the phylogenetic analyses have varied considerably among these studies, a general picture of the evolutionary relationships of the megalocytiviruses has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Iridoviruses are large DNA viruses and result in global amphibian declines and heavy economic losses in aquaculture industry [3]. Singapore grouper iridovirus (SGIV), a novel ranavirus belonging to family Iridoviridae, was first isolated from the brown-spotted grouper [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine candidate strain is a very crucial factor for development and application of an effective cell-cultured vaccine [34]. Although it is still unclear whether serological difference exists among different megalocytiviral strains, a previous report suggested that phenotypic diversity exists in different viral strains, even that those strains belong to completely the same genotype cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is still unclear whether serological difference exists among different megalocytiviral strains, a previous report suggested that phenotypic diversity exists in different viral strains, even that those strains belong to completely the same genotype cluster. The phenotypic diversity maybe lead to significant differences in viral replication in vitro, virulence to host fish and viral antigenicity for vaccine development [34]. For instance, in Shinmoto et al's report, RSIV-U-6 based cell vaccine could achieve 69% protective effect in immunized red sea bream juveniles.…”
Section: Discussionmentioning
confidence: 99%